Narrativas dos usuários de um CAPS AD : a dimensão sociocultural e os modos de subjetivação frente à política de "Guerra às drogas" - Branco, Nicéia Maria Malheiros Castelo (2017)
The "War on Drugs" Policy has spread the idea of a drug-free world, which is the cause of all the ills of society. The news in the media, under the title "Crack Epidemy”, materialized in urban spaces with the famous Cracolândias, have disseminated in the cultural imaginary the idea of the crazy/drug user with idea of violence and criminality. What triggered this study was our concern about the importance of the Sociocultural Dimension of Psychiatric Reform, which consists to intervene in the cultural issue in society, but it has not been very effective in the complexity involving drugs and drug users. We seek to understand what and how the crossings of this "War on Drugs", materialized by the Abstinence Paradigm, interfere in the care under the perspective of the Harm Reduction Paradigm and Psychosocial Care, whose principles are based on the National Policy on Mental Health, Alcohol and Other Drugs. Our intention was to listen how those directly involved in this issue, users and users attended in a CAPS AD, are affected by the speeches, practices and effects in their modes of subjectivation and in the alternatives of care that they resort to. We use intervention research, since we understand that the researcher who conceives human experiences as unique and who has an ethical-political and aesthetic commitment to the reality on which she works, makes this an important way for us to effectively produce knowledge in defense of life and citizenship of the individuals. We conducted five weekly meetings, using the methodology of the press conference, with a group of 18 participants, 13 men and 5 women. Based on what emerged in the narratives and our concerns, we grouped the discussions into five topics: drugs; perspective and ideas about people who use drugs; what they think of care; the religious question and the dreams, the desires and the utopias think. In this course, listening to these users, we point out clues so that we can intervene in the sociocultural dimension and advance in the process of the Brazilian Psychiatric Reform.